2-D analytical model of surface potential for graded-channel-double-gate (GCDG) MOSFETs - Goel V.; Kumar A.; Rout S.S.; Maurya A.K.; Sharma S.; Kumar S. (My University, 2025)
This paper presents a 2-D analytical model of surface potential for graded-channel-double-gate (GCDG) MOSFETs to discuss the benefits of incorporation of graded-channel in double-gate (DG) MOSFET. The 2-D analytical modeling is based upon the solution of Poisson's equations in channel region(s) exploring parabolic channel potential profile and excluding the effects of interface charges. The surface potential dependency on the variation of drain bias and doping is also discussed. The results obtained from the analytical model have been discussed to demonstrate the figure of merit of GCDG structure over Double Gate (DG) structure. To validate the analytical model results, the results obtained from analytical model have been compared with numerical simulation data obtained by 2-D device simulator, SILVACO ATLAS™. © 2016 IEEE.